A memória institucional do Instituto Histórico e Geográfico Paraibano: perspectivas dos seus sujeitos institucionais - Vieira, Thullio Santos (2021)
This research copes with the idea of the phenomenon of Institutional Memory in the context of a memory institution with more than a century of institutional history: the Instituto Histórico e Geográfico Paraibano (IHGP). The general objective of this research focuses on investigating the phenomenon of Institutional Memory within the scope of the IHGP. In order to achieve this general objective, the respective specific objectives were: to describe the IHGP historically and institutionally; discuss the Institutional Memory construct in the IHGP; characterize the phenomenon of Institutional Memory in the IHGP. It is based on the study “Institutional Memory” by Icléia Thiesen (2013) as a theoretical framework. This research has a qualitative approach, analyzing the documents through the methodology of Aróstegui (2006) for the documentary study. As a data collection instrument, the research used a semi-structured interview, applied individually to the institutional subjects of the IHGP, who act as servants and partners of the institution. For data analysis and treatment, we adopted Content Analysis to identify the characteristics of the Institutional Memory phenomenon at the IHGP through the speeches of the institutional subjects. As a result of the research, the speeches of the institutional subjects are presented, organized in three general categories: the subjects' conceptions about the Institutional Memory of the IHGP; actions and obstacles to preserve the Institutional Memory of the IHGP; and the instruments and channels that reframe and share the Institutional Memory of the Institute. Through the elements presented, we observed similarities and differences in the speeches of the institutional subjects about the Institutional Memory of the IHGP regarding institutional performance, historical representativeness and the institute's documents.